(untitled) (Revista de Ciências Agroveterinárias, 2022)
Lettuce is the main leafy vegetable commercialized in Brazil and it is cultivated in many different environment conditions and regions. But, under high temperature and high light intensity lettuce plants tend to early flowering, making it difficult to obtain high-quality lettuce harvest. Thus, this study was aimed to evaluate the productive performance of lettuce cultivars in a greenhouse in the municipality of Humaitá, Amazonas state (AM). The cultivars used were Rafaela and Hanson, Veneranda, Mônica SF 31, Simpson, Solaris, Elba, Quatro Estações and Babá de Verão. The lettuce seedlings were transplanted 24 days after sowing into a greenhouse covered by 100 micra polyethylene transparent agrofilm. It was used bed with 33-m-long and 1-m-wide, using 30 cm x 30 cm spacing between plants. The experimental design was randomized complete block with four replications. The parameters evaluated 32 days after transplanting were plant diameter, number of leaves, stem length and shoot dry mass. Cultivars Babá de Verão and Elba presented a better agronomic performance for cultivation in greenhouse in municipality of Humaitá, Amazonas state.